Serum HIF-1α Levels, miR-210 Expressions, and Reactive Oxygen Species Levels in Early Abortion and Normal Pregnancy - Serudji, Joserizal; Irawati, Nuzulia; Mose, Johanes Cornelius; Ali, Hirowati; Yusrawati, Yusrawati (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: The blastocyst implants in a relatively hypoxic state. Hypoxic state triggers hypoxia-inducible factor-1α (HIF-1ɑ) production, upregulates the transcription factor miR-210, and stimulates reactive oxygen species (ROS) production by trophoblast cells. HIF-1α also increases the expression of miR-210. High expression of micro-RNA 210 (miR-210) suppresses mitochondrial respiration, increasing ROS production. High level of ROS may result in DNA damage or cell disfunction, thereby impaired trophoblast invasion, leading to early abortion. This study aims to determine the differences of serum HIF-1ɑ levels, miR-210 expressions, and ROS levels between early abortion and normal pregnancy. Method: This cross-sectional comparative study was conducted in Dr. M. Djamil Hospital Padang, Andalas University Hospital, and 5 Public Health Centers in Padang. Fifty-patients with gestational age less than 12 weeks (25 early abortions and 25 normal pregnancies) were included in this study. All samples were tested for HIF-1ɑ and ROS level using enzyme-linked immunosorbent assay (ELISA) method, and miR-210 expression using real-time polymerase chain reaction (PCR) technique. Spearman correlation and Mann Whitney test. was used in this study. Results: Both study groups were equivalent in terms of age, gestational age, and gravidity (p = 0.51, 0.453 and 1.00). The median of HIF-1ɑ level, miR-210 expression, and ROS level were higher in early abortions than normal pregnancies i.e (3.73 vs 3.42) ng/mL (p = 0.016), (43.55 vs 17.85) copies/ng (p = 0.027), and (1.36 vs 1.20) ng/mL (p = 0.003). The coefficient correlations were 0.16 between HIF-1ɑ level and miR-210 expression (p=0.267), 0.46 between HIF-1ɑ level and ROS level (p=0.001), and 0.18 between miR-210 expression and ROS level (p=0.207). Conclusion: HIF-1ɑ level, miR-210 expression, and ROS level were associated with early abortion. HIF-1ɑ level has a correlation with ROS level.